Caesarean section-related blood transfusion: risk factors in a private teaching hospital in Nigeria - Salami, Omotayo F.; Akadri, Adebayo A.; Imonitie, Clifford (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Comprehensive emergency obstetric care, which includes the life-saving procedure of blood transfusion, is one of the essential components of effective emergency obstetric care that leads to a reduction in maternal mortality. In this study, blood transfusion risk factors were found in patients who had Caesarean deliveries at our facility. Methods: This was a retrospective study of all pregnant women who had caesarean section at Babcock University Teaching Hospital, Nigeria between 2016 and 2020. Their medical records were retrieved and reviewed using pro-forma. Chi square analysis was used to determine significant association between blood transfusion status and independent variables. Information was extracted from medical records using pro-forma. Results: Of 1568 obstetric admissions, there were 1210 deliveries and 369 (30.5%) caesarean sections. Ninety-five women (25.7%) of those that had caesarean sections were transfused. The incidence of blood transfusion was 13.7%. The preoperative packed cell volume, age and caesarean delivery type were significantly associated with blood transfusion status (p<0.05). Conclusions: Preoperative anemia, age and caesarean delivery type were all associated with blood transfusion status. To maximize hemoglobin levels at delivery and to identify high-risk patients, regular antenatal checkups should be given more importance.